A creative industries perspective on open strategy drivers - Radomska, Joanna; Wołczek, Przemysław; Hajdas, Monika; Klimczak, Mikołaj (Publishing House of Wroclaw University of Economics and Business, 2024)
Open strategy is a widely discussed research area, including the themes of organization design, open innovation, and open business models. However, the contextual perspective to analyse this concept is scarce. This paper addressed this issue by providing a framework highlighting a set of drivers that may affect transparency and inclusiveness as dimensions of open strategy and proposed these drivers by exploring the context of the creative industries representing the activities that differ in their business ecosystem. However, they are very similar in some respects (e.g., generating ideas, imagination, copyrights, intellectual property). These similarities make it interesting to bring the CI as the context for investigating industry factors that impact the strategy’s opening to understand the drivers that may hinder or foster its implementation. The authors believe the proposed framework could guide the decision-making process by providing the unfavourable and conducive drivers that might affect open strategy implementation.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 162-178